The foundation of the schools of infancy in Bologna (1836-1850) (Foro de Educacion, 2011)
From the beginning of the XIXth century, in many Italian countries a different new sen- sibility developped about children, both for philatropic and social reasons. Too many poor children in the streets living alone for all the day, without the loving care of their parents working in factories, started a social emergency that needed the intervention of local authorities, together with the charity of well-born families. Philantropic society were founded in order to help the government to solve this social danger, and to compell children to go to school for building a better community for the future. So many women joined the associa- tions and they set the aim to create new istitutions for very young children. In Bologna, a group of nobles and high-level women helped to start this project, working to collect money. But the beginning was not so good, and the final result came only in 1847.